PENGARUH KUALITAS PELAYANAN DAN KUALITAS PRODUK TERHADAP KEPUASAN PELANGGAN JASA APLIKASI BISATOPUP PT. AMANAH KARYA INDONESIA JAKARTA - Mona Karina; Imam Fauzi (ITB Swadharma, 2021)
This study aims to determine the effect of Service Quality and Product Quality on Customer Satisfaction. The number of respondents is 54 users of the bisatopup application in the South Jakarta area. The analysis used in this research is using SPSS 21.0 software. The analysis technique uses multiple regression analysis with least-squares equations and hypothesis testing using t-statistics and F-test to test the regression coefficients partially and simultaneously, test validity, test reliability, and test classical assumptions which include normality test, multicollinearity test, and heteroscedasticity test. The results showed that: There is a positive and significant effect between service quality and customer satisfaction. There is a positive and significant effect between product quality and customer satisfaction. So it can be concluded that the quality of service and product quality together affect customer satisfaction